Skin-Limited Graft-versus-Host Disease after Pancreatic Transplantation - Muneeb Ilyas; Elika Hoss; David J. DiCaudo; Hasan Khamash; Mark R. Pittelkow; Amit Sharma (Case Reports in Transplantation)
Introduction. The phenomenon of graft-versus-host disease, a solid organ transplant recipient, is a rare development with a very poor prognosis. Case Presentation. A 40-year-old woman with type 1 diabetes developed cutaneous graft-versus-host disease following second pancreas transplantation. Conclusion. The development of a nonspecific rash in the early posttransplant period following a pancreas transplant warrants suspicion for graft-versus-host disease.